2012
DOI: 10.1097/tp.0b013e31823b2d8e
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Diagnosis, and Treatment of Chylous Leakage After Laparoscopic Live Donor Nephrectomy

Abstract: CL is a potentially insidious and perhaps misdiagnosed complication after LLDN. It occurs in nearly 4% of LLDN and it seems to be uniquely associated to left-sided kidney recovery because of distinctive lymphatics distribution around the periaortic area of dissection. Conservative therapy is effective in most donors and should be initially attempted. Surgical ligatures or fibrin sealants may be indicated in case of refractory CL before the arising of malnutrition and/or relevant immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Incidence of chylous ascites ranged from 0.17% to 2% in gynecological pelvic surgery (3)(4)(5), 1.0% to 6.6% in colorectal surgery (6-8), 4.7% in hepatic surgery including liver transplantation (9), 3.8% to 5.1% in nephrectomy (10,11), and 1.0% to 11% in pancreatic surgery (1, [12][13][14][15][16][17][18][19]. The incidence of chylous ascites in patients with abdominal drainage after pancreatic surgery did not differ significantly from those patients without drainage (20).…”
Section: Incidencementioning
confidence: 99%
“…Incidence of chylous ascites ranged from 0.17% to 2% in gynecological pelvic surgery (3)(4)(5), 1.0% to 6.6% in colorectal surgery (6-8), 4.7% in hepatic surgery including liver transplantation (9), 3.8% to 5.1% in nephrectomy (10,11), and 1.0% to 11% in pancreatic surgery (1, [12][13][14][15][16][17][18][19]. The incidence of chylous ascites in patients with abdominal drainage after pancreatic surgery did not differ significantly from those patients without drainage (20).…”
Section: Incidencementioning
confidence: 99%
“…Meticulous and extensive clipping remains the safest way of securing lymphatic channels along the dissection area. 10 It has been shown that bipolar cautery can effectively ligate and control lymph leakage. Using bipolar cauterizing, we have not seen 1 case of lymph leakage after more than 1500 laparoscopic donor nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Boggi and associates report 8 cases of 208 LLDN successfully treated with conservative measures, providing further insight into both anatomicbasis and available therapeutic options. 10 Breda and associates 8 described 2 cases of chylous ascites, both patients were treated with low-fat, medium-chain triglyceride (MCT) diet. The chyle leak resolved after 2 weeks of conservative management, but the dietary regimen modifications were prolonged for 6 months to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations